2018
DOI: 10.3389/fpls.2018.00905
|View full text |Cite
|
Sign up to set email alerts
|

Legume Intercropping With the Bioenergy Crop Sida hermaphrodita on Marginal Soil

Abstract: The cultivation of perennial biomass plants on marginal soils can serve as a sustainable alternative to conventional biomass production via annual cultures on fertile soils. Sida hermaphrodita is a promising species to be cultivated in an extensive cropping system on marginal soils in combination with organic fertilization using biogas digestates. In order to enrich this cropping system with nitrogen (N) and to increase overall soil fertility of the production system, we tested the potential of intercropping w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…In addition, successful intercropping of miscanthus with yellow melilot could improve the biodiversity conservation effects and landscape appearance of miscanthus compared with miscanthus cultivated alone and miscanthus intercropped with WAM. Furthermore, it is expected that yellow melilot contributes to soil fertility and provides additional nitrogen (N) fixation, as has been reported for intercropping Virginia mallow (Sida hermaphrodita L. Rusby) and white melilot (Melilotus albus L.) [71].…”
Section: Yellow Melilot and Miscanthus (Yam)mentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, successful intercropping of miscanthus with yellow melilot could improve the biodiversity conservation effects and landscape appearance of miscanthus compared with miscanthus cultivated alone and miscanthus intercropped with WAM. Furthermore, it is expected that yellow melilot contributes to soil fertility and provides additional nitrogen (N) fixation, as has been reported for intercropping Virginia mallow (Sida hermaphrodita L. Rusby) and white melilot (Melilotus albus L.) [71].…”
Section: Yellow Melilot and Miscanthus (Yam)mentioning
confidence: 94%
“…Another question to be addressed is which other legume species would be suitable for intercropping with miscanthus. According to Nabel et al (2018) [56,71], who reported on the suitability of Virginia mallow for legume-intercropping, possibilities include red clover (Trifolium pratense L.), white clover (Trifolium repens L.), and lucerne (Medicago sativa L.). Other legume species worth investigating are common bird's-foot trefoil (Lotus corniculatus L.) and hop clover (Medicago lupulina L.).…”
Section: Recommendations For Future Investigationsmentioning
confidence: 99%
“…Conversely, the utilization of marginal agricultural land often promises to improve its overall value, or at least to maintain its current resilience and protect it from further degradation [55]. Many studies have revealed significant evidence to support the positive social-ecological effects of bioenergy crop cultivation on marginal agricultural land depending on the selected bioenergy crops and BCS, respectively [47,52,[86][87][88][89][90]. Some dedicated bioenergy crops for cultivation on marginal agricultural land are shown in Figure 1.…”
Section: The Potential Social-ecological Contribution Of Bioenergy Crmentioning
confidence: 99%
“…Recent studies have shown that cultivating the species Sida hermaphrodita (L.) Rusby with maize does not reduce biomass when intercropped with legumes, but that biomass is reduced significantly when intercropped with grasses (Nabel et al. , Weidlich et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…development of native species (Longo et al 2011). Recent studies have shown that cultivating the species Sida hermaphrodita (L.) Rusby with maize does not reduce biomass when intercropped with legumes, but that biomass is reduced significantly when intercropped with grasses (Nabel et al 2018, Weidlich et al 2018). In addition, attention must be given to green manure seed density at planting since high biomass coverage can result in lower light availability, hindering the growth of native species under legume intercropping .…”
Section: Discussionmentioning
confidence: 99%